Solidarność Dolnośląska . pismo MKZ NSZZ "Solidarność" z siedzibą we Wrocławiu, no. 5, 1980 - [ed. Stanisław Huskowski, Krzysztof Turkowski, Maciej Zięba] (MKZ NSZZ "Solidarność", 1980)
Print run: 10000 copies